Lived secularity: religious living in a secular age - Hedges, Paul (2023)
Sometimes secularism is understood in monolithic ways, especially in opposition to religious ways of life. But religion and secularism are not opposites. Religious people can be fully committed to secularism, and in lived secularity we see many ways religious and non-religious people negotiate their position within complex societies.